2021
DOI: 10.1155/2021/9923378
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Treatment Outcome in Patients with TB-HIV Coinfection in Kuala Lumpur, Malaysia

Abstract: Background. Tuberculosis (TB) is a serious health threat to people living with human immunodeficiency virus (HIV). This study aimed to identify the characteristics, unsuccessful TB treatment rate, and determinants of unsuccessful TB treatment outcome among patients with TB-HIV coinfection in Kuala Lumpur. Methods. This was a cross-sectional study. The data of all patients with TB-HIV in the federal territory of Kuala Lumpur from 2013 to 2017 were collected and reviewed. The data were retrieved from the nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In this study, it was found that men had the highest proportion (84.82%) of TB/HIV coinfection, which is consistent with the findings of other studies [ 15 , [38] , [39] , [40] ]. However, a study conducted in South Africa by Mahtab et al reported that coinfection was more prevalent in women than in men [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, it was found that men had the highest proportion (84.82%) of TB/HIV coinfection, which is consistent with the findings of other studies [ 15 , [38] , [39] , [40] ]. However, a study conducted in South Africa by Mahtab et al reported that coinfection was more prevalent in women than in men [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…This study found that patients coinfected with TB and HIV took longer to recover from TB, with an average treatment duration of 11 months compared to 8 months for other TB patients. However, other studies have reported different average durations, such as 8.30 months in Teng et al's study [ 50 ], and 6–12 months in another study for 48.10% of patients [ 15 ], but these studies did not compare TB/HIV coinfected patients to other TB patients. Hayibor et al's study reported a treatment duration of more than 6 months for both HIV-positive and HIV-negative groups, while the two groups did not differ from each other [ 43 ], which contradicts the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with physical or cognitive impairment that prevent them from being able to answer the questions were excluded. The treatment protocol of TB patients enrolled in this study has been previously reported [10,11].…”
Section: Study Settings and Population Sourcementioning
confidence: 99%